2012
DOI: 10.1016/j.physb.2012.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Orientation selection of equiaxed dendritic growth by three-dimensional cellular automaton model

Abstract: A three-dimensional (3-D) adaptive mesh refinement (AMR) cellular automata (CA) model is developed to simulate the equiaxed dendritic growth of pure substance. In order to reduce the mesh induced anisotropy by CA capture rules, a limited neighbor solid fraction (LNSF) method is presented. An expansion description using two interface free energy anisotropy parameters ( 1 ,  2 ) is used in present 3-D CA model. The dendrite growths with the orientation selection between <100> and <110> are discussed using the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…The evolution behavior of the organization is often affected by the anisotropy of the mesh, thus restricting the accuracy of the prediction of CA model. L. Wei et al [11] used adaptive mesh technology (limited neigh-bor solid fraction, LNSF) which can reduce mesh anisotropy and modified the previous model.…”
Section: Coupling Principle Of Cafementioning
confidence: 99%
“…The evolution behavior of the organization is often affected by the anisotropy of the mesh, thus restricting the accuracy of the prediction of CA model. L. Wei et al [11] used adaptive mesh technology (limited neigh-bor solid fraction, LNSF) which can reduce mesh anisotropy and modified the previous model.…”
Section: Coupling Principle Of Cafementioning
confidence: 99%
“…It has been reported that these models can quantitatively reproduce most experimentally observed dendritic structures within acceptable computational timeframes. [6][7][8][9][10][11][12][13] The CA model has been combined with adaptive mesh refinement 11) or with a multi-grid method [6][7][8][9][10]12,13) because the related computational times depend on grid sizes for calculating temperature, solute concentrations, and solid fraction fields.…”
Section: Introductionmentioning
confidence: 99%
“…Using this model, the effect of the anisotropic surface energy on the dendrite growth kinetics and morphologies was studied. In order to reduce the mesh induced anisotropy caused by CA capture rules, a 3-D CA model coupled with a limited neighbor solid fraction, referred to as the LNSE method, was developed by Wei et al [22], as this model was suitable for use in describing the solidification of a pure substance. In this model, two interface free energy anisotropy parameters were employed in order to simulate the dendrite orientation selection.…”
Section: Introductionmentioning
confidence: 99%